Penggunaan Teknologi Berbasis Internet Dalam Pelaksanaan Terapi Kognitif Perilaku untuk Insomnia (Online CBT-I) : Tinjauan Pustaka - Ida Ayu Kartikasari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
The incidence of insomnia can be found in almost every age range. Cognitive behavioral therapy for insomnia is one of the therapies that can be chosen to overcome insomnia. Technological developments in the world of health have also been adapted to cognitive behavioral therapy interventions for insomnia. This article aims to explore the use of internet-based technology in the implementation of cognitive behavioral therapy for insomnia. The literature review of this article was obtained from the online databases of Google Scholar, ProQuest, Science Direct, SpringerLink and ClinicalKey in the 2017-2022 publication year. The use of internet-based technology in the implementation of cognitive behavioral therapy for insomnia offers easy access, flexibility, privacy and comfort for clients. Better effectiveness was also shown compared to behavioral cognitive therapy for face-to-face insomnia.